2021
DOI: 10.31234/osf.io/nxkgp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual Desire in the Time of COVID-19: How COVID-Related Stressors are Associated with Sexual Desire in Romantic Relationships

Abstract: The COVID-19 pandemic and social distancing measures caused widespread social and economic disruptions, resulting in spikes in unemployment and financial instability, along with drastic changes to people's ability to feel socially connected. These changes could have implications on people’s sex lives as external stressors, like those introduced amidst the COVID-19 pandemic, are risk factors for depressive symptoms, which are associated with lower levels of sexual desire. The current research (N = 4,993) examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“… Balzarini, Muise, Zoppolat, Gesselamn et al’s (2022) findings highlight the connective influences of sexual desire, identity factors, and individual health outcomes in building a more comprehensive understanding of how relational partners function in a crisis. However, they are in conflict with Brotto et al (2021) , who found that higher dyadic sexual desire was associated with increased COVID-19 stress in a Canadian sample and that higher COVID-19 stress also was linked to greater sexual coercion, which did not change over time ( Brotto et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 93%
See 2 more Smart Citations
“… Balzarini, Muise, Zoppolat, Gesselamn et al’s (2022) findings highlight the connective influences of sexual desire, identity factors, and individual health outcomes in building a more comprehensive understanding of how relational partners function in a crisis. However, they are in conflict with Brotto et al (2021) , who found that higher dyadic sexual desire was associated with increased COVID-19 stress in a Canadian sample and that higher COVID-19 stress also was linked to greater sexual coercion, which did not change over time ( Brotto et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 93%
“… Balzarini, Muise, Zoppolat, Gesselman et al (2022) examined almost 5000 participants from 57 different countries who were in romantic relationships to determine how sexual desire changed over time in response to external stressors and whether external stressors introduced by COVID-19 were risk factors for depressive symptoms, which, in turn, decreased sexual desire. They found that, at the onset of the pandemic, stress decreased sexual desire toward one’s partner, whereas financial concern and worry over COVID increased it, with no significant effects for biological sex ( Balzarini, Muise, Zoppolat, Gesselman et al, 2022 ). When the effects were examined over time, external stressors like worry about COVID and stress were now detrimental to sexual desire.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Using online pornography alone during lockdown might have been a way to satisfy one's sexual needs at the onset of the pandemic, particularly when the partner was unavailable or uninterested in having sex (Hille et al, 2021). Building upon other studies (Balzarini et al, 2021;Luetke et al, 2020), this behavior possibly added strains to the relationship and may have predisposed people to experience lower sexual desire or sex quality caused by pandemic-related stressors. In contrast, using online pornography with the partner might have been a way to add sexual novelty to the relationship (Lehmiller et al, 2021), possibly helping some of the pandemic-related strains and enhancing perceived sex life quality, but this behavior was not translated into sexual satisfaction or partner intimacy.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the demographic characteristics, multiple psychological variables are related to sexual activity. Higher risk perception of COVID-19, anxiety, stress and depression were negatively associated with the frequency of sexual activity and satisfaction [49,52,53,61]. On the contrary, those who experienced fewer disruptions in their daily lives felt more sexual desire and reported better sexual functioning [62].…”
Section: Sexuality During the Pandemicmentioning
confidence: 98%